Image processing analysis to determine fajr time using the imagej application - Septianto, Arif; Rosalina, Rosalina; Ramza, Harry (ILKOM Jurnal Ilmiah, 2021)
The issue of determining the time of prayer is very fundamental because it is one of the pillars so that the worship of a Muslim is accepted. The government has set a standard for carrying out the dawn prayer, namely by determining the degree of appearance of the dawn of shodiq at -20 degrees. This study aims to compare the initial determination of the government's dawn time using different sensors, namely drones as image sensors, drones were chosen because they have several advantages. The resulting data is in the form of photos and then the photo data is processed using digital image processing software, namely imagej. The data from imagej processing are in the form of mean and standard deviation, all data are then recapitulated using Microsoft excel and plotted so as to form data which is then carried out by a polynomial approach to determine the cutoff point as an early indicator of the entry of dawn. The method used in this study is using a qualitative analysis method with a polynomial 5 approach. The conclusion obtained in this study is that the government's dawn time is 21 minutes faster, the standard used in this study is a DIP of -13.95 degrees and unlike the 2D SQM. 3D drone data results in more accurate data analysis and is not easy to manipulate because it can be verified with photo data.